Predictive Factors and Strategies to Prevent the Development of Type 2 Endoleaks following Endovascular Aneurysm Repair - Voutsinas, Nicholas; Kim, Edward; Lookstein, Robert A. (Seminars in Interventional Radiology, 2020)
Type 2 endoleaks are a potential complication of endovascular aortic repair for abdominal aortic aneurysms. They are caused by vessels that have been excluded from the aorta lumen, but may still fill the aneurysm sac due to collateral filling. Type 2 endoleaks may lead to increased morbidity and need for additional procedures. Being able to identify patients at risk for Type 2 endoleaks and prevent them is important for any physician who is performing endovascular aortic repair.
Keywords: abdominal aortic aneurysm; endovascular repair; endoleak; preoperative embolization; interventional radiology